Analisis Kadar Hemoglobin Perokok Aktif dan Pasif pada Lingkungan Komunitas Musik di Kota Batu - Putro, Kristian Syah (Jaringan Laboratorium Medis, 2025)
Active smokers and passive smokers are widely found throughout the world, this is due to the negative influence from the surrounding environment which causes an increase in the number of cigarette consumers as well as someone who is exposed to cigarette smoke every day. The purpose of this study was to determine the hemoglobin levels of active smokers and passive smokers in musicians in the Batu City music community. This research method uses descriptive analytical research with a cross-sectional approach. The research sample consisted of 33 venous blood of active smokers and passive smokers in musicians in the Batu City music community. The examination was carried out using the cyanmethomoglobin method. The results found that the average normal male hemoglobin level was 15.8 g / dL with a frequency of 9, and high 19.1 g / dL as many as 16 frequencies, while for normal women 13.4 g / dL with a frequency of 3, for high 15.7 g / dL with a frequency of 5. The results of the Pearson correlation data analysis showed that there was a relationship between hemoglobin levels and active smokers and passive smokers with a value of P 0.01. Active smokers and passive smokers have differences in hemoglobin levels, high hemoglobin levels are dominated by active smokers, namely 75% and normal hemoglobin levels are dominated by passive smokers, namely 54%. This means that it can be concluded that there are differences in hemoglobin levels in active smokers and passive smokers of musicians in the Batu City music community. So the right advice for respondents is to reduce smoking gradually and then choose other positive activities rather than having to consume cigarettes every day.